A Clean and Facile Synthesis Strategy of MoS2 Nanosheets Grown on Multi-Wall CNTs for Enhanced Hydrogen Evolution Reaction Performance - Cao, Jiamu; Zhou, Jing; Zhang, Yufeng; Liu, Xiaowei (Scientific reports, 2017)
Unique hybrid nanostructure, which consists of multi-wall carbon nanotube (MWCNT) stems and MoS 2 nanosheet (NS) leaves, are prepared by a hydrothermal method. The fabricated material can be potentially used as an electrocatalyst for the hydrogen evolution reaction (HER). To our knowledge, as the reaction medium, water is firstly utilized to the synthesis of the 1T phase MoS 2 NSs which uniformly grow on the carbon-based materials. As a result, a nanohybrid catalyst with excellent HER electrocatalytic properties, which included an onset potential of as low as 50 mV, a Tafel slope of 43 mV dec −1 , and remarkable cycling stability, is produced. The observed outstanding catalytic performance can be attributed to the uniform distribution of the metallic 1T phase of the MoS 2 NSs, which are characterized by the presence of multiple active edges as well as the effective electron transport route provided by the conductive MWCNT substrate. This work demonstrates the high potential of the synthesized HER catalyst and proposes a novel, efficient, environmentally friendly, and inexpensive method for its fabrication.